2019
DOI: 10.1093/imrn/rnz018
|View full text |Cite
|
Sign up to set email alerts
|

A Moving Lemma for Algebraic Cycles With Modulus and Contravariance

Abstract: We prove a moving lemma which implies the contravariance of Bloch-Esnault's additive higher Chow group in smooth affine varieties and Binda-Saito's higher Chow group (taken in the Nisnevich topology) in smooth varieties equipped with effective Cartier divisors. The new ingredients in the moving method are parallel translation with modulus in the affine space that involves a new integer parameter, and Noether's normalization lemma over a Dedekind base.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…When X is effective, the relative motivic cohomology is introduced in [6]. If moreover X • is smooth, the relative motivic cohomology is contravariantly functorial with respect to coadmissible left fine (not necessarily flat) morphisms of modulus pairs ( [8]). We do not know whether this is true for non-effective modulus pairs or not.…”
Section: A Results On Relative Motivic Cohomologiesmentioning
confidence: 99%
“…When X is effective, the relative motivic cohomology is introduced in [6]. If moreover X • is smooth, the relative motivic cohomology is contravariantly functorial with respect to coadmissible left fine (not necessarily flat) morphisms of modulus pairs ( [8]). We do not know whether this is true for non-effective modulus pairs or not.…”
Section: A Results On Relative Motivic Cohomologiesmentioning
confidence: 99%
“…For different counter-examples to the descent property, see [43], before Theorem 3. On the bright side, we mention the following important result recently obtained by W. Kai (see [29,Theorem 1.4]). If (X, D) and (Y , E) are two pairs of schemes of finite type over k equipped with effective Cartier divisors, we say that a morphism f : X → Y is an admissible morphism of pairs if f * E is defined as Cartier divisor on X and f restricts to a morphism D → E. Remark 2.13.…”
mentioning
confidence: 82%
“…There are some new results which provide a ground for the optimistic choice of the words. Kai [29] established a moving lemma for cycle complexes with modulus which implies an appropriate contravariant functoriality of the Nisnevich version of (1.3) (see Theorem 2.12 for the precise statement). A work by Iwasa and Kai [27] provides Chern classes from the relative K -groups of the pair (X , D) to the Nisnevich motivic cohomology groups H * M,Nis (X |D, Z( * )), while a construction of the first author [3, Theorem 4.4.10] (see also [4,Theorem 3.5]) gives cycle classes from the groups of higher 0-cycles with modulus CH d+n (X |D, n) to the relative K -groups K n (X , D).…”
mentioning
confidence: 99%
“…Although recently established results by various authors (see [Kai16], [RS16]) have indicated that the Chow groups with modulus (and, more generally, the relative motivic cohomology groups of [BS16]) have some of the above expected properties, many questions remain widely open.…”
Section: Introductionmentioning
confidence: 99%